Species of the genus Heteralonia Bezzi, 1921 from China (Diptera: Bombyliidae) - Yao, Gang; Yang, Ding; Evenhuis, Neal L. (Zootaxa, 2009)
The following four new species of the genus Heteralonia from China are described and illustrated: Heteralonia anemosyris sp. nov., Heteralonia cnecos sp. nov., Heteralonia nigripilosa sp. nov., and Heteralonia ochros sp. nov. A key to the species of the genus Heteralonia from China is presented.